Modelagem de software de tempo real utilizando o profile MARTE da UML - Silvestre, Eduardo Augusto (2012)
Object-oriented methods and languages have been widely applied in activities of modeling and design of real-time systems. Among all object-oriented notations, UML is the most used one. Despite the many well-known issues both in theory and practice, such as lack of concepts to represent time constraints and resource allocation, UML has been frequently applied to this domain. The MARTE profile was proposed in order to solve these issues. In this work the MARTE profile is applied together with UML to modeling a software for traffic signals control in order to analyze the pros and cons of using this recent OMG profile. The MARTE profile is compared with UML and SPT (a former MARTE profile). The result is that with MARTE the models are more specific and expressive, but are also more complex. In addition, mastering the MARTE language is a hard challenge. Researches and industrial applications are still required to achieve better conclusions on the use of MARTE.